The Using of Paper-mode Quizizz in EFL Classroom - Rezkyana, Dika; Agustini, Dian; Nurtika, Auliya (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2022)
This study aims to investigate EFL teachers’ perception on developing lesson plans on curriculum 2013. There are 16 teachers of English in Junior High School in Cilacap who participated in this study. To investigate teacher’s perceptions, questionnaires and interview were used. Guttman and Likert scale questionnaires were used to collect their insights on developing a lesson plan. An interview was administered to get in-depth information about teachers’ perceptions of developing lessons plans. The finding indicates that teachers of English have a negative perception on developing lesson plans. They feel unhappy, not encouraged, and unenthusiastic, even when they realize the developing lesson plan would facilitate and achieve their objective in teaching English. Unpredictably, the MGMP lesson plan product arises as resistance in developing a lesson plan. It is proposed to the teacher who implements curriculum 2013 to be creative and innovative to fulfill teaching objectivesThe study examines how English as a Foreign Language (EFL) teachers view the process of creating lesson plans under the Curriculum 2013 framework. Sixteen English teachers from junior high schools in Cilacap participated in the research. The researchers used questionnaires and interviews to gather information. They employed Guttman and Likert scale questionnaires to collect teachers' opinions on lesson plan development. Interviews were conducted to obtain more detailed insights. The results show that the teachers generally have a negative attitude towards developing lesson plans. They feel unhappy, unmotivated, and unenthusiastic about the process, even though they understand that lesson plans help them achieve their teaching goals. Unexpectedly, the study found that the MGMP (subject teachers' association) lesson plan product acts as a barrier to individual lesson plan development. This suggests that teachers may be relying on pre-made plans rather than creating their own. The researchers recommend that teachers implementing Curriculum 2013 should be creative and innovative in their approach to meet their teaching objectives, rather than relying solely on standardized plans.